2022
DOI: 10.1155/2022/9185384
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Acupuncture and Moxibustion Combined with Needle-Knife on Pain and Lumbar Function in Patients with Lumbar Disc Herniation

Abstract: This study aimed for the analysis of the effect of acupuncture and moxibustion combined with needle-knife on pain and lumbar function in patients with lumbar disc herniation. From June 2019 to February 2021, the medical records of 126 patients with lumbar disc herniation admitted to the department of orthopedics of our hospital were selected and divided into the control group (n = 63) treated with acupuncture and moxibustion and the observation group (n = 63) treated with acupuncture and moxibustion combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Acupotomy therapy is the method of treating abnormal, cicatricial, or contracted soft tissues with microtrauma using the needle-knife. Clinically, it has proven to be effective in China and is widely used by clinicians ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acupotomy therapy is the method of treating abnormal, cicatricial, or contracted soft tissues with microtrauma using the needle-knife. Clinically, it has proven to be effective in China and is widely used by clinicians ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of research and the expansion of clinical indications, some scholars have found that acupuncture and moxibustion can also intervene in the perioperative adjuvant treatment of modern surgery, which has potential advantages in relieving postoperative pain, promoting the recovery of motor function and accelerating rehabilitation. [ 6 , 7 ] Based on the above effects, some clinical workers have combined acupuncture with PTED to treat LDH, showing more prominent postoperative rehabilitation effects. [ 8 , 9 ] This means that patients will have less pain after surgery, a shorter recovery time, and less hospital expenses.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%